(untitled) (Research, Society and Development, 2023)
Beta-alanine supplementation has been widely used as a dietary supplement to improve physical performance. Its positive effects are associated with increased muscle carnosine, which provides greater resistance and reduced fatigue during training in different sports. That said, this article aims to presents a narrative review that explores the benefits of beta-alanine supplementation on sports performance and its influence on body composition. The review also focuses on the role of beta-alanine in the formation of carnosine, a dipeptide compound naturally present in the human body. The results highlight that beta-alanine has benefits in physical performance, with only one easily avoided side effect, contributing to the improvement of endurance and reduction of muscle fatigue during resistance training. The investigated studies demonstrate that beta-alanine supplementation contributes to the better development of exercise, raising carnosine levels and minimizing the feeling of fatigue, resulting in improved physical performance.